2015
DOI: 10.1149/2.1131509jes
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for Controllable Fabrication of Porous Anodic Aluminum Oxide Templates with Multiple-Scale Structures

Abstract: Porous anodic aluminum oxide (AAO) templates with diverse nano/submicron/micron multiple-scale structures have been fabricated by a facile and controllable two-step anodization process. The first step anodization has been achieved by using a simple competitive growth process with high anodization voltage (U a ) in ethanol-oxalic acid mixture electrolytes. The effects of U a (300-600 V), anodization current density (J a , 100-200 A m −2 ), and the proportion of ethanol adding (0.3 M oxalic acid : ethanol = 1 : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Moreover, Li et al developed a new approach to fabricate porous AAO films with multi-scale nano-micro structures. 6 The numerous AAO growing processes were introduced for high-quality AAO but monitoring AAO processes was an accompanied crucial issue. Some AAO related reviews reported the fundamental aspects of film growth including ionic transport under intense electric fields, highly uniform thickness over a large area and anodic polarization developed in suitable electrolytes.…”
mentioning
confidence: 99%
“…Moreover, Li et al developed a new approach to fabricate porous AAO films with multi-scale nano-micro structures. 6 The numerous AAO growing processes were introduced for high-quality AAO but monitoring AAO processes was an accompanied crucial issue. Some AAO related reviews reported the fundamental aspects of film growth including ionic transport under intense electric fields, highly uniform thickness over a large area and anodic polarization developed in suitable electrolytes.…”
mentioning
confidence: 99%
“…[34][35][36] Accordingly, finding proper methods for the fabrication of AAO with various controllable microstructures has become a hot topic. 11,[34][35][36][37][38][39][40][41][42][43][44][45][46] Among these methods, conducting anodization processes on patterned aluminum surface instead of the smooth one, has been known as one of the most effective ways for obtaining unique AAO structures. [39][40][41][42][43] Therefore, finding facile, low-cost, controllable and repeatable methods for preparing patterned aluminum surface, thus obtaining diverse unique AAO structures, is significant from the viewpoint of both fundamental research and practical applications.…”
mentioning
confidence: 99%
“…51,52 However, most of these porous AAO films were fabricated based on smooth aluminum surface. Considering that performing anodization processes on patterned aluz E-mail: msliyi@scut.edu.cn minum surface is one of the most effective ways for obtaining unique AAO structures, [39][40][41][42][43] comparative studies have been done based on smooth aluminum surface and patterned aluminum surface.…”
mentioning
confidence: 99%
See 2 more Smart Citations